Peningkatan Kapasitas Pelaku Industri Rumahan melalui Pelatihan Pemanfaatan Teknologi Informasi dan Komunikasi di Kabupaten Lombok Timur - Samsu, L M; Muhammad Saiful; Hariman Bahtiar; Muh.Adrian Juniarta; Yupi Kuspandi Putra (Jurnal Teknologi Informasi untuk Masyarakat, 2025)
This community service activity aims to enhance the capacity of home-based industry actors in East Lombok Regency through training on the utilization of Information and Communication Technology (ICT). The main challenges faced by small business actors in this area include limited access to digital technology and a lack of skills in leveraging ICT to support business activities, particularly in promotion, financial record-keeping, and online product marketing. Using a participatory approach, the training activities covered basic computer usage, the use of social media as a marketing tool, and an introduction to e-commerce platforms. Evaluation results showed a significant improvement in participants’ knowledge and skills, as reflected in their ability to manage digital business accounts, expand marketing reach, and optimize the use of business-supporting applications. This activity is expected to serve as a model for digital technology-based economic empowerment in rural areas. Keywords: ICT training, home industry, empowerment, MSMEs, East Lombok